SUSTAINABLE DYEING OF TEXTILES USING TOMATO WASTE EXTRACTS: INFLUENCE OF FESO₄ MORDANT ON COLOR QUALITY - Fadiyah Ayu Rahmawati; Emmidia Djonaedi; Rachmah Nanda Kartika (Universitas Negeri Jakarta, 2025)
The use of tomato waste as an effort to reduce the accumulation of organic waste and environmental pollution due to textile dyeing requires mordantt material as a color fixer. This study aims to analyze the effectiveness of iron Fe(SO₄) mordantt in dyeing cotton fabrics using natural dyes from tomato waste extract. The research was carried out by an experimental method, namely by dyeing textiles in the form of cotton cloth with dyeing techniques using the results of tomato waste extracts with variations in mordantt iron concentrations, namely 0%, 2%, 5%, and 7%. The staining results were analyzed using a spectrodensitometer to measure the CIEL*a*b* value and test the color fastness to light. The results showed that 7% iron mordant produced the most intense red-yellow color with an L* value of 64.38, an a* value of 28.7, and a b* value of 51.22. The staining results with a 7% iron mordantt had a very good color fade resistance value (scale 4-5), while the sample without a mordant had a very poor fade resistance (ΔE=25.19). Iron mordant Fe(SO₄) has been proven to have good effectiveness in producing more intense colors in fabric dyeing results and increasing color fastness in textile dyeing results with tomato waste extract.